Medical-Surgical nursing : (Elsevier Health Sciences, 2014)
Over the past three decades, more and more nursing educators have turned to Lewis: Medical-Surgical Nursing for its accurate and up-to-date coverage of the latest trends, hot topics, and clinical developments in the field of medical-surgical nursing ― and the new ninth edition is no exception! Written by a dedicated team of expert authors led by Sharon Lewis, Medical-Surgical Nursing, 9th Edition offers the same easy-to-read style that students have come to love, along with the timely and thoroughly accurate content that educators have come to trust. Completely revised and updated content explores patient care in various clinical settings and focuses on key topics such as prioritization, critical thinking, patient safety, and NCLEX® exam preparation. Best of all ― a complete collection of interactive student resources creates a more engaging learning environment to prepare you for clinical practice.